STUDY OF DIRECT INJECTION COMPRESSED NATURAL GAS ENGINE EMPLOYING EXHAUST GAS RECIRCULATION WITH HYDROGEN GAS AS A DUAL FUEL - SAHEED OLALEKAN, WASIU (2013)
Spark ignition engine fuelled by hydrogen enriched compressed natural gas (H-CNG) engine have numerous benefits compared to conventional engine like gasoline, diesel and natural gas engine especially in emission control. Many researchers have continuously conducting experimental researches to improve HCNG engine and adopt a strategy aimed at realizing an improved performance with good fuel consumption and least possible out emission, most especially nitric oxide emission (NOx) emission. Thus, an experimental study has been conducted to study performance, emission and combustion characteristics of the direct injection compressed natural gas engine employing exhaust gas recirculation with hydrogen gas as a dual fuel (i.e. DI-HCNG-EGR) at relative air-fuel ratios (i.e. A= 0.9, 1.0, 1.1, 1.2, 1.3 and 1.4) which represent rich, stoichiometric, slightly lean, moderately lean, lean and very lean mixtures respectively.